Educating boys and girls equally: principles of gender-sensitive Islamic parenting - Dwi Ratnasari; Luqyana Azmiya Putri (Universitas Negeri Yogyakarta, 2026)
Differential treatment of boys and girls in parenting and education has led to inequality. The reality of the dual roles often imposed on women demonstrates a complexity that is not easy to navigate. Childhood is an important period because it is during this phase that an individual's personality begins to form and children begin to explore themselves. This can be minimized through equal and proportional educational parenting patterns for both boys and girls. To that end, this study aims to explore the principles of Islamic parenting with a gender perspective. This paper describes the efforts that must be made in raising and educating children with a gender perspective. The research method used is a library research approach. The collected data was then analyzed using content analysis techniques. The results of the study show that one of the principles of gender-sensitive Islamic parenting is framed in the concept of hadhanah. Child rearing based on gender values provides equal opportunities for boys and girls to develop their potential in order to realize a just and peaceful society in accordance with the spirit of Islamic values.